A Facile Chemical-Free Cathode Powder Separation Method for Lithium Ion Battery Resource Recovery. (October 2020) - Jafari, Milad; Torabian, Mohammad Mahdi; Bazargan, Alireza
Highlights: Cathode powder was separated from Al foil using heating and ultrasonic treatment Ultrasonication greatly improved the removal efficiency The process was optimized and an applied workflow was suggested The concentration of valuable metals increased 2-3 fold compared to raw batteries No harmful chemicals were used during the process Abstract: The high cost of primary materials and their limited resources, as well as the ever-increasing amount of waste, has magnified the need for recycling and resource recovery from lithium ion batteries (LIB). This need will only be exasperated in the future as personal electronic equipment and electric vehicles (EV) become more widespread. In this study, a simple process for the separation of the cathode materials from waste Apple iPhone 6 lithium batteries is proposed, consisting of thermal treatment followed by ultrasonication. The main advantages of the process are its simplicity and complete independence from all chemicals. Heating the cathode material to 550°C gradually increases the removal efficiency; however, further increase in temperature results in a sharp decline of removal due to changes in the Al foil structure. With limited aeration inside the muffle furnace the removal barely exceeded 60%, whereas under suitable aeration, removal efficiencies exceeding 90% were obtained. Ultrasonication aids the release of cathode powder by creating convective flow as well as intense cavitation. As ultrasonication time and power increase, so does the removal efficiency. However, by increasing the power from 50 W to 100 W, the cathode powder separation efficiency decreases. This is because the numerous cavitation bubbles create a barrier for the transmission of acoustic energy to other parts of the tank, meaning the physical vibration of the transducer is greater than the fluid's ability to stay in contact. The final obtained cathodic powder under optimum conditions (heating for 15 min at 550°C, followed by ultrasonic treatment at 45°C and 50 Watts for 1 min) was 45.5% Co, 4.9% Al, 13.7% Cu, 3.6% Li, and 13.7% Ni. Graphical abstract: Image, graphical abstract